'To Holmgard … and Beyond': Folk metal fantasies and hegemonic white masculinities. (1st September 2015) - Spracklen, Karl
On first inspection, the metal music subgenre of folk metal might be arguably residual white, masculine spaces. The subgenres are not fashionable within the metal music scene. Folk metal bands are ridiculed by fans of black metal for being too mainstream and crowd-pleasing, constructing fantasies of drinking and fighting that have no authentic connection to Vikings, Saxons or other (supposed) nationalist patriarchs. But folk metal bands are not part of the mainstream of modern heavy metal, judged by sales of records and numbers of fans on social media. This article draws on new research on folk metal and its reputation within heavy metal, using a range of Internet sources and semiotic analysis of folk metal bands' songs and images. The bands at the focus of the case study research are bands that have been deliberately selected because they are well-established in the industry, and generally known to fans of heavy metal: Turisas (Finland), Týr (Faroe Islands), Eluveitie (Switzerland), In Extremo (Germany) and Cruachan (Ireland). In this article, I argue that folk metal is not easily dismissed as a fantasy space for young, white European men left behind by postmodernity, postcolonialism and a rearrangement of the gender order. Rather, folk metal remains central to the ongoing construction of heavy metal as a form of commodified leisure that makes the power of western, instrumental whiteness and hegemonic masculinity invisible, while ironically being in plain sight.